2019
DOI: 10.1007/s10584-019-02431-8
|View full text |Cite
|
Sign up to set email alerts
|

Storm surge return levels induced by mid-to-late-twenty-first-century extratropical cyclones in the Northeastern United States

Abstract: We investigate the impact of climate change on the storm surges induced by extratropical cyclones (ETCs) between November and March. We quantify changes to the storm surge between a historical period and a future period during the mid to late twenty-first century (2054-2079) for a number of major coastal cities in the Northeastern United States. Observed water levels are analyzed to estimate storm surges induced by ETCs during the historical period. A hydrodynamic model is utilized to simulate storm surges in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 34 publications
6
50
1
1
Order By: Relevance
“…A multilinear regression method using derived surface wind stress and sea-level pressure from several CMIP5 models under the RCP8.5 scenario found little change in storm surges for the NYC area from present day to 2054-2079 [160]. Moreover, by using a hydrodynamic model forced with six hourly 10-m winds and sea-level pressures, only small increases were found in surge heights for a number of coastal cities along the Northeastern US Coast for the same models, time period, and scenario [161]. Nonetheless, there are relatively large uncertainties, since one climate model predicted a 25-40% increase in surge heights.…”
Section: Coastal Flooding and Wave Damagementioning
confidence: 85%
“…A multilinear regression method using derived surface wind stress and sea-level pressure from several CMIP5 models under the RCP8.5 scenario found little change in storm surges for the NYC area from present day to 2054-2079 [160]. Moreover, by using a hydrodynamic model forced with six hourly 10-m winds and sea-level pressures, only small increases were found in surge heights for a number of coastal cities along the Northeastern US Coast for the same models, time period, and scenario [161]. Nonetheless, there are relatively large uncertainties, since one climate model predicted a 25-40% increase in surge heights.…”
Section: Coastal Flooding and Wave Damagementioning
confidence: 85%
“…After terrain correction, we fitted the data using the classic Gumbel's Type I extreme value distribution. Assuming that this distribution is stationary over time [e.g., Roberts et al (2017) and Lin et al (2019) found that extratropical cyclones are not likely to change much with climate change], we combined it with the time-varying extreme value distribution of TC wind speeds to determine the design wind speed of a mixed climate. Specifically, given a target LEP (p) and design lifetime period (m), the design wind speed (x d ) is determined numerically from…”
Section: Estimation Of Design Wind Speed Based On Lepmentioning
confidence: 99%
“…Despite their relatively infrequent occurrence along the northern portion of the U.S. Atlantic Coast, these surge events have produced substantial damages. In particular, the NJ‐NY region is characterized by these low‐frequency and high‐impact TC‐ and extratropical (Booth et al, ; Colle et al, ; Lin et al, ; Needham et al, ) cyclone‐induced storm surge events. Most notable are the Long Island Express Hurricane (1983), which produced storm surge of 3.0–3.5 m in Long Island (Lin et al, ), and more recently Hurricane Sandy (2012), a transitioning extratropical cyclone that tested the resilience of the NJ‐NY coastal region with typical storm surge heights of about 3–4 m (Blake et al, ).…”
Section: Introductionmentioning
confidence: 99%